Structural stability and spatial increase of ash pond dykes in thermal power stations - Mittal, Satyendra; Wayal, Vaishali (Journal of Structural Engineering, 2024)
The fly ash is stored in the form of dykes in thermal power stations. Stability of these dykes is affected when further raising of these dykes is done. In the present paper stability measures with spatial consideration have been discussed. It is seen that the gabion faced reinforced fly ash wall not only ensures the stability of dykes against sliding failure but also creates extra space for storage of new ash. The factor of safety of 1.35 of the mother dyke at the stage of it’s fully fill condition increases to 4.96 by construction of such wall with also creation of substantial storage space for new ash. Such walls are highly cost effective and structurally balanced.